Ruimte, identiteit en beweging in Tommy Wieringa se Joe Speedboot (2005) - Aldrich, Catrina (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Afrikaans and Dutch))--University of Stellenbosch, 2010.